RE-ESTABLISHING ECOLOGICAL RELATIONS IN THE WORLDVIEW OF MENTAWAI INDIGENOUS RELIGION - Wahyuni, Dwi; Sabna, Anjali (UIN Sumatera Utara Medan, 2025)
Indigenous religion studies, particularly Arat Sabulungan in Mentawai, are dominated by the world religion paradigm, resulting in biased representations labeled